Effect of β-blockers on mortality in patients with sepsis: A propensity-score matched analysis - Ge, Cheng-Long; Zhang, Li-Na; Ai, Yu-Hang; Chen, Wei; Ye, Zhi-Wen; Zou, Yu; Peng, Qian-Yi (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives: We aimed to evaluate the association between β-blocker therapy and mortality in patients with sepsis. Methods: Patients with sepsis were selected from the Medical Information Mart for Intensive Care (MIMIC)-III. Propensity score matching (PSM) was used to balance the baseline differences. A multivariate Cox regression model was used to assess the relationship between β-blocker therapy and mortality. The primary outcome was the 28-day mortality. Results: A total of 12,360 patients were included in the study, involving 3,895 who received β-blocker therapy and 8,465 who did not. After PSM, 3,891 pairs of patients were matched. The results showed that β-blockers were associated with improved 28- (hazards ratio (HR) 0.78) and 90-day (HR 0.84) mortality. Long-acting β-blockers were associated with improved 28-day survival (757/3627 [20.9%] vs. 583/3627 [16.1%], P < 0.001, HR0.76) and 90-day survival (1065/3627 [29.4%] vs.921/3627 [25.4%], P < 0.001, HR 0.77). Short-acting β-blocker treatment did not reduce the 28-day and 90-day mortality (61/264 [23.1%] vs. 63/264 [23.9%], P = 0.89 and 83/264 [31.4%] vs. 89/264 [31.7%], P = 0.8, respectively). Conclusions: β-blockers were associated with improved 28- and 90-day mortality in patients with sepsis and septic shock. Long-acting β-blocker therapy may have a protective role in patients with sepsis, reducing the 28-day and 90-day mortality. However, short-acting β-blocker (esmolol) treatment did not reduce the mortality in sepsis.